"Legst du ihre Himmelsschrift auf die Erde an?" (Ijob 38,33) - Was aber meint "Himmelsschrift"? - Boeckle, Jakob (Old Testament Essays, 2022)
Since the hapax legomenon מִשְׁטָר* of Job 38:33b is understood as a “scripture of heaven,” its meaning can be deduced only from the environment of the Old Near East but in particular from its context, Job 38:31–33 (including Job 9:9). Thus, the separate consideration of the verbs, “link, loosen, lead out, guide” and of the constellations, “Pleiades, Orion, Hyades, Big Bear over its cubs, chambers of the South” (Job 38:31–32; 9:9) – including the parallel “orders of heaven” (Job 38:33a) and altogether by God’s rhetorically ironic challenge of Job – proves what can be understood in detail and as a whole under מִשְׁטָר*: as a script written in the sky of the God who treats the aforementioned constellations (representing the entire astronomical cosmic world) and their cosmic orders as their Creator, Lord and Shepherd and makes them work on earth. It can apply in general but also beyond the Book of Job: human (and thus the suffering Job) is able to read this writing for the renewed perception of God and, depending on the circumstances, to apply it on earth (e. g. in agriculture). https://doi.org/10.17159/2312-3621/2022/v35n2a7